'RING US IF YOU NEED US': THE IMPORTANCE OF REASSURANCE TO FAMILY CAREGIVERS PROVIDING HOME-BASED END-OF-LIFE CARE. Issue 1 (1st March 2014) - Dunn, L; Byrne, P; Lloyd-Williams, M
Abstract : Introduction: This research explores the experience of uncertainty and reassurance from the perspective of family carers. Aim(s) and method(s): To explore the phenomenological experience of providing end of life care for a family member with a life-limiting illness, at home. Fifty-one narrative interviews were conducted with bereaved family carers. Data was analysed using thematic structural analysis (Robichaux 2003; Riessman 2008). Results: Uncertainty emerged as a key feature of the caregiving experience. Many carers were invited by community health care professionals to 'ring us if you need us'. However, carers explained that they were reluctant to telephone about non-emergency issues. In some cases, this led to feelings of isolation, uncertainty about pain and symptom management and uncertainty as their relative approached death. By contrast, carers explained that they would feel more reassured if they had received additional contact from health and social care professionals to 'check up' on them and 'see how they were doing'. Additionally, scheduled visits from community and district nurses were a great source of reassurance to many carers. Feelings of uncertainty were greatest in the days and hours approaching their relative's death. Conclusion(s): Health care professionals working in the community may have limited awareness of the important impact that their presence has in reassuring family caregivers and improving their confidence in caring. In addition, increased informal contact made by health and social care professionals may reduce carers' uncertainty in providing end-of-life care at home.